Sensory exotropia due to keratoconus and review of the literature - Ciftci S (Dove Medical Press, 2013)
Suleyman Ciftci,1 Ali Simsek,2 Eyup Dogan,1 Leyla Ciftci31Department of Ophthalmology, Diyarbakir Training and Research Hospital, Diyarbakir; 2Department of Ophthalmology, Faculty of Medicine, Adiyaman University, Adiyaman; 3Department of Cardiology, Faculty of Medicine, Dicle University, Diyarbakir, TurkeyAbstract: This case report describes a 17-year-old boy with sensory strabismus due to keratoconus and an ipsilateral nodular lesion of the bulbar conjunctiva. The aligned eye was the right eye and keratoconus in this eye was of late onset. Vision in the left eye was poor and keratoconus was advanced in this eye. Due to the longstanding nature of the keratoconus and its occurrence in a developmentally sensitive period, sensory exotropia had developed in the left eye. There was a nodular lesion of the bulbar conjunctiva in the ipsilateral eye. If keratoconus occurs before the age of 7 years and the prolonged visual loss is not corrected, sensory strabismus can develop, as in this patient.Keywords: keratoconus, sensory exotropia, childhood